Energy management in plastics processing : strategies, targets, techniques, and tools - Kent, Robin John (Elsevier, 2018)
Energy Management in Plastics Processing: Strategies, Targets, Techniques, and Tools, Third Edition, addresses energy benchmarking and site surveys, how to understand energy supplies and bills, and how to measure and manage energy usage and carbon footprinting. The book's approach highlights the need to reduce the kWh/kg of materials processed and the resulting permanent reductions in consumption and costs. Every topic is covered in a 2-page spread, providing the reader with clear actions and key tips for success. This revised third edition covers new developments in energy management, power supply considerations, automation, assembly operations, water footprinting, and transport considerations, and more. Users will find a practical workbook that not only shows how to reduce energy consumption in all the major plastics shaping processes (moulding, extrusion, forming), but also provides tactics that will benefit other locations in plants (e.g. in factory services and nonmanufacturing areas).